2012
DOI: 10.1038/clpt.2012.96
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics Knowledge for Personalized Medicine

Abstract: The Pharmacogenomics Knowledgebase (PharmGKB) is a resource that collects, curates, and disseminates information about the impact of human genetic variation on drug responses. It provides clinically relevant information, including dosing guidelines, annotated drug labels, and potentially actionable gene–drug associations and genotype–phenotype relationships. Curators assign levels of evidence to variant–drug associations using well-defined criteria based on careful literature review. Thus, PharmGKB is a useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
1,407
1
25

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,601 publications
(1,468 citation statements)
references
References 4 publications
9
1,407
1
25
Order By: Relevance
“…According to assignment of allele function ( CYP2C19 allele definition table) and citations for allele function that are posted on PharmGKB [31] (accessed on February, 2018), the phenotypic status of the CYP2C19 metabolizing activity is classified into ultra-rapid, rapid, normal, intermediate or poor metabolizer, depending on the genotypic combination (or diplotye) of an individual. Table 2 lists the several CYP2C19 haplotypes/diplotypes based on genotype determinations and the related metabolizer phenotypes.…”
Section: Cyp2c19 Polymorphisms and Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to assignment of allele function ( CYP2C19 allele definition table) and citations for allele function that are posted on PharmGKB [31] (accessed on February, 2018), the phenotypic status of the CYP2C19 metabolizing activity is classified into ultra-rapid, rapid, normal, intermediate or poor metabolizer, depending on the genotypic combination (or diplotye) of an individual. Table 2 lists the several CYP2C19 haplotypes/diplotypes based on genotype determinations and the related metabolizer phenotypes.…”
Section: Cyp2c19 Polymorphisms and Phenotypesmentioning
confidence: 99%
“…One report of five healthy individuals (four NM; one PM) has shown that dexlansoprazole clearance was 12% of its clearance in individuals with NM phenotype [22]. Despite the limited data on the impact of CYP2C19 , the FDA labeling of dexlansoprazole, accessed through PharmGKb [31]-included pharmacogenetic information that documented 12-fold and twofold increases in dexlansoprazole AUC in Japanese individuals with PM and IM phenotype compared to NM, suggesting that dexlansoprazole is also influenced by CYP2C19 genotype.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one well studied PGx relationship is G6PD:202A-chloroquine-anemia, which states that patients with the version 202A of the gene G6PD and treated with chloroquine (an antimalarial drug) may present an anemia (an abnormally low level of red blood cells in blood). These knowledge units (i) are available in reference databases, such as PharmGKB [14], reported in the scientific biomedical literature and (ii) may be discovered by mining clinical data such as Electronic Health Records (EHRs). Therefore, knowledge in PGx is heterogeneously described (i.e., with various quality, granularity, vocabulary, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…And yet, genetic testing is recommended or required by the United States Food and Drug Administration (US FDA) for only 39 drugs, many of the genetic markers predate the discoveries made by GWAS. 21 Here we perform a SWOT analysis examining the strengths, weaknesses, opportunities and threats around the role of pharmacogenomics in public health and clinical medicine. The outcome of our analysis explains the dichotomy between the accelerated pace of discovery and the sluggish uptake of pharmacogenomics in standard clinical care.…”
Section: Introductionmentioning
confidence: 99%